Design of Arduino Uno-based laboratory glove box with UV lamp, blower, and DHT22 sensor for learning media - Hikmah Maya Sari; Rakhmad Rizkiansyah; Muhammad Akbar Hariyono (Pelita International Publishing, 2025)
A laboratory glove box is a customized instrument that allows users to manipulate things in a controlled environment. It creates a different atmosphere within a chamber and can also be used as a sterilizer. The project named Design and Build a Laboratory Glove Box Using UV Lamps and Blower Equipped with a DHT 22 Sensor Based on Arduino Uno for Learning Media' seeks to improve the quality of student learning. Using this glove box, students can gain a better understanding of fundamental ideas, operational methods, and standard operating protocols for laboratory glove box equipment. The feasibility tests, including validation by media experts and material experts, indicate that ' ‘Design and Build a Laboratory Glove Box Using UV Lamps and Blower Equipped with a DHT 22 Sensor Based on Arduino Uno for Learning Media' is highly suitable for practical use